Mechano-transduction in periodontal ligament cells identifies activated states of MAP-kinases p42/44 and p38-stress kinase as a mechanism for MMP-13 expression - Ziegler, Nelli; Alonso, Angel; Steinberg, Thorsten; Woodnutt, Dale Anne; Kohl, Annette; Müssig, Eva; Schulz, Simon; Tomakidi, Pascal (BMC cell biology, 2010)
Mechano-transduction in periodontal ligament (PDL) cells is crucial for physiological and orthodontic tooth movement-associated periodontal remodelling. On the mechanistic level, molecules involved in this mechano-transduction process in PDL cells are not yet completely elucidated.
Published: 28 January 2010
Gesehen am 09.02.2024